Effect of the use of chestnuts (Castanea sativa Miller) in the finishing diet of Celta pig breed on the shelf-life of meat refrigerated and frozen. (December 2018) - Echegaray, Noemí; Domínguez, Ruben; Franco, Daniel; Lorenzo, José M.; Carballo, Javier
Abstract: The effect of the use of commercial feed or chestnuts ( Castanea sativa Miller) in the finishing diet of Celta pig on the microbiological counts, physicochemical parameters (pH and color), myoglobin state, lipid and protein oxidation, and sensory attributes of Longissimus dorsi muscle packaged in modified atmospheres during the refrigerated storage (28 days at 4 °C) was investigated. Also, the effect on the physicochemical parameters (pH and color), myoglobin state, lipid and protein oxidation, and sensory attributes of meat during frozen storage (180 days at −20 °C) was studied. The use of chestnuts in the finishing diet significantly increased the counts of the different microbial groups (total aerobic mesophilic bacteria, total aerobic psychrotrophic bacteria, lactic acid bacteria, and Enterobacteriaceae) during refrigerated storage of meat. However the use of chestnuts did not affect significantly the values of pH, color parameters, percentages of the myoglobin forms, lipid and protein oxidation or sensory attributes of the meat during the refrigerated or frozen storage. The microbiological and oxidative parameters indicated an acceptable quality of meat after 28 days of refrigerated storage; however, judges found the sensory attributes modified after 12 or 20 days of storage. Highlights: The effect of the finishing diet of pigs on the shelf-life of meat was investigated. Finishing diet of chestnuts or commercial feed were essayed. Chestnuts diet increased the microbial counts along the refrigerated storage. Finishing diet did not affect the shelf-life of meat refrigerated. Shelf-life of frozen meat was also independent of the finishing diet.